2021
DOI: 10.1073/pnas.2025383118
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hyperpolarization and purification of the metabolite fumarate in aqueous solution

Abstract: Hyperpolarized fumarate is a promising biosensor for carbon-13 magnetic resonance metabolic imaging. Such molecular imaging applications require nuclear hyperpolarization to attain sufficient signal strength. Dissolution dynamic nuclear polarization is the current state-of-the-art methodology for hyperpolarizing fumarate, but this is expensive and relatively slow. Alternatively, this important biomolecule can be hyperpolarized in a cheap and convenient manner using parahydrogen-induced polarization. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 30 publications
2
119
0
Order By: Relevance
“…Many such catalysts can achieve pairwise addition of H 2 to a substrate and/or to a catalytically active cen-ter, which is usually a prerequisite for parahydrogen-based hyperpolarization. At the same time, there are several significant reasons why PHIP via heterogeneous hydrogenations (HET-PHIP) (Balu et al, 2009;Gutmann et al, 2010;Kaltschnee et al, 2019;Kovtunov et al, 2013Kovtunov et al, , 2016Kovtunov et al, , 2020a) can be advantageous. In particular, in vivo applications certainly require catalyst-free hyperpolarized fluids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many such catalysts can achieve pairwise addition of H 2 to a substrate and/or to a catalytically active cen-ter, which is usually a prerequisite for parahydrogen-based hyperpolarization. At the same time, there are several significant reasons why PHIP via heterogeneous hydrogenations (HET-PHIP) (Balu et al, 2009;Gutmann et al, 2010;Kaltschnee et al, 2019;Kovtunov et al, 2013Kovtunov et al, , 2016Kovtunov et al, , 2020a) can be advantageous. In particular, in vivo applications certainly require catalyst-free hyperpolarized fluids.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, most heterogeneous catalysts demonstrated a limited efficiency in the pairwise hydrogen addition, in some cases low yields of the desired product, or both (Balu et al, 2009;Gutmann et al, 2010;Kaltschnee et al, 2019;Kovtunov et al, 2013Kovtunov et al, , 2016Kovtunov et al, , 2020a. Better heterogeneous catalysts are thus required, something which is constantly searched for in heterogeneous catalysis in general as more active and selective industrial catalysts have a major impact on all areas of our life.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperpolarized fumarate can be purified by acid precipitation as a pure solid, and later redissolved at a chosen concentration in a clean aqueous solvent. It was found that it is possible to form hyperpolarized fumarate at several hundred millimolar concentrations, at 13 C polarization levels of 30–45% (see Knecht et al 77 ). Rodin et al 127 have developed efficient and robust strategies to convert the proton spin order of fumarate into polarization of 13 C nuclei.…”
Section: Applications Of Parahydrogen In Nmrmentioning
confidence: 99%
“…It was shown that fumarate can be precipitated, filtered out and redissolved, with the hyperpolarization preserved during the phase transformations [150] . In the recent studies, it was demonstrated that the hyperpolarized fumarate aqueous solution at 13 C polarization levels of 24–45 % is produced using such approach [151,152] …”
Section: Applications Of Heterogeneous Phipmentioning
confidence: 99%